Role of insulin-like growth factor, insulin-like growth factor receptors, and insulin-like growth factor-binding proteins in ovarian cancer - Periyasamy Amutha; Thangarajan Rajkumar (Indian Journal of Medical and Paediatric Oncology)
Insulin and IGFs play an important role in cancer initiation and progression, including ovarian cancer (OC). Epithelial ovarian cancer (EOC) is the most frequent type of OC in women and it is the most lethal gynecological malignancy worldwide. Generally, insulin is associated with metabolism, whereas Insulin like growth factors (IGFs) are involved in cell proliferation. Hence, Insulin-like growth factor binding proteins (IGFBPs) determines the bioavailability of IGFs in circulation. The interplay between these molecules such as insulin, IGFs, IGFBPs and insulin-like growth factor receptor 1 (IGF1R) may be crucial for ovarian cancer cell biology and cancer progression. However, the IGF1R inhibitors exhibiting potent activity on IGF/IGF1R also demonstrated activity against OC cells. The combination therapy of drugs may prove to be beneficial in clinical management of OC. This review describes both molecular and clinical associations between insulin and IGF1 signaling pathways in ovarian cancer. The data was collected using PubMed search engine with the following key words such as ovarian cancer, IGFs, IGFBP, IGF1Rs and ovarian cancer.